Halochromic properties and antimicrobial potential of crude extracts from five species of ornamental plants (UNED Research Journal, 2019)
Introduction: the colours of flowers are a result of secondary metabolites that have long been used in the medical and textile industries, and those that are halochromic are used in colour display because they change color according to pH changes, but many species are yet to be studied in detail. Objective: to explore the halochromic properties and the antimicrobial potentials of the crude extracts of several ornamental plants. Methods: we used aqueous and organic solvents to extract pigments from petals of five fascinating flowers planted around International Institute of Tropical Agriculture station, Cotonou, Benin: Allamanda blanchetii, Cascabela thevetia, Eichhornia crassipes, Ixora casei and Thunbergia erecta, followed by an investigation into their halochromic properties. Antibacterial potentials of the extracts were tested on important rice pathogens: Xanthomonas oryzae pv. oryzae, and Pantoea agglomerans, which are gram-negative bacteria; and on Bacillus subtilis, a gram-positive bacterium. Results: The crude extracts of T. erecta and A. blanchetii have good halochromic properties within pH 2 – 12, exhibiting distinct colours. The chromophores of the C. thevetia, E. crassipes, and I. casei are not halochromic as the colours of the crude extracts remain the same at the pH range except pH 12 which is similar for the five extracts. Crude extracts of T. erecta inhibited growth of P. agglomerans without development of resistance, whereas the bacteria developed resistance against Penicillin after 18 hrs of incubation. T. erecta and A. blanchetii were able to inhibit growth of X. oryzae and both inhibited B. subtilis. Conclusion: Pigments from both T. erecta and A. blanchetii are good pH indicators; however, T. erecta is a better antibacterial agent than A. blanchetii because it has broad-spectrum activities against bacteria.
Keywords: antimicrobial; halochromism; Thunbergia erecta; anthocyanin; Xanthomonas oryzae pv. oryzae; Pantoea agglomerans; Bacillus subtilis